Traps African American Men on Gender and Sexuality - Byrd, Rudolph P.; Guy-Sheftall, Beverly (Indiana University Press, 2001)
Traps is the first anthology that historicizes the writings by African American men who have examined the meanings of the overlapping categories of race, gender, and sexuality, and who have theorized these categories in the most expansive and progressive terms. Traps contains the landmark speeches, essays, letters, and a manifesto by nineteenth- and twentieth-century African American men who have examined the complex terrain of gender and sexuality within the historical and cultural matrix of the United States.